2011
DOI: 10.1080/00036841003689739
|View full text |Cite
|
Sign up to set email alerts
|

First-author conditions: evidence from finance journal coauthorship

Abstract: We study the trend and the author name-ordering rule in finance publication using the publication records of 21 core finance journals during the period from 1990 to 2004. We empirically model the underlying factors that affect the alphabetical ordering rule among multi-authored finance articles. We find that the choice of alphabetical ordering is based on the quality of the article, institutional heterogeneity, team size and cultural factors. The central argument rests upon the need to signal and the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…The results in Brown et al . () with respect to the average co‐author affiliation suggest that co‐authors from lower ranked institutions have a greater incentive to signal their relative contribution by not using alphabetic ordering than do co‐authors from higher ranked institutions. To test that here, a variable measured as the average rank of the university affiliation of the co‐authors ( AUTHRANK ) is included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results in Brown et al . () with respect to the average co‐author affiliation suggest that co‐authors from lower ranked institutions have a greater incentive to signal their relative contribution by not using alphabetic ordering than do co‐authors from higher ranked institutions. To test that here, a variable measured as the average rank of the university affiliation of the co‐authors ( AUTHRANK ) is included.…”
Section: Methodsmentioning
confidence: 99%
“…Brown et al . () modelled and empirically tested the use of alphabetic name ordering in finance journals. They found that alphabetic name ordering was more likely when the article quality was higher (as measured by journal quality), the co‐authors were affiliated with higher ranked university departments, the research team was smaller, and European authors were on the research team…”
Section: Methodsmentioning
confidence: 99%
“…On the level of individual scholars, quality and quantity of a scholar's academic output are widely used for salary and promotion decisions (Brown et al, 2011). With the help of co-authoring, scholars might be able to optimize these parameters: Aside from stimulating higher contextual quality, teamwork allows each author participate in multiple projects at the same time (Acedo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, researchers publish to distribute their generated knowledge (Hangel & Schmidt-Pfister, 2017). However, as several science studies show, researchers also publish to increase their reputational capital in the competition for jobs, tenure, promotion, salary, and funding (Brown, Chan, & Chen, 2011;Merton, 1973;Moore, Newman, & Turnbull, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Economics use alphabetic name ordering to display equal contributions, and an expectance of coauthors to engage in and to contribute equally to the research process (Brown et al, 2011;Engers, Gans, Grant, & King, 1999). Engers et al (1999) state that it is an equilibrium for economists to use alphabetic author order, since all authors receive the same recognition and therefore provide equal contributions.…”
Section: Introductionmentioning
confidence: 99%